Flavokawain A induces apoptosis in MCF-7 and MDA-MB231 and inhibits the metastatic process in vitro. - Nadiah Abu; M Nadeem Akhtar; Swee Keong Yeap; Kian Lam Lim; Wan Yong Ho; Aimi Jamil Zulfadli; Abdul Rahman Omar; Mohd Roslan Sulaiman; Mohd Puad Abdullah; Noorjahan Banu Alitheen (PLoS ONE)
Introduction The kava-kava plant (Piper methsyticum) is traditionally known as the pacific elixir by the pacific islanders for its role in a wide range of biological activities. The extract of the roots of this plant contains a variety of interesting molecules including Flavokawain A and this molecule is known to have anti-cancer properties. Breast cancer is still one of the leading diagnosed cancers in women today. The metastatic process is also very pertinent in the progression of tumorigenesis. Methods MCF-7 and MDA-MB231 cells were treated with several concentrations of FKA. The apoptotic analysis was done through the MTT assay, BrdU assay, Annexin V analysis, cell cycle analysis, JC-1 mitochondrial dye, AO/PI dual staining, caspase 8/9 fluorometric assay, quantitative real time PCR and western blot. For the metastatic assays, the in vitro scratch assay, trans-well migration/invasion assay, HUVEC tube formation assay, ex vivo rat aortic ring assay, quantitative real time PCR and western blot were employed. Results We have investigated the effects of FKA on the apoptotic and metastatic process in two breast cancer cell lines. FKA induces apoptosis in both MCF-7 and MDA-MB231 in a dose dependent manner through the intrinsic mitochondrial pathway. Additionally, FKA selectively induces a G2/M arrest in the cell cycle machinery of MDA-MB231 and G1 arrest in MCF-7. This suggests that FKA's anti-cancer activity is dependent on the p53 status. Moreover, FKA also halted the migration and invasion process in MDA-MB231. The similar effects can be seen in the inhibition of the angiogenesis process as well. Conclusions FKA managed to induce apoptosis and inhibit the metastatic process in two breast cancer cell lines, in vitro. Overall, FKA may serve as a promising candidate in the search of a new anti-cancer drug especially in halting the metastatic process but further in vivo evidence is needed.